Collaborative Grounded Theory - Kara L. Vander Linden; Catherine J. Tompkins (Grounded Theory Review: An International Journal, 2021)
This article describes how two researchers’ professional relationship began as a mentor/mentee relationship and transformed into co-researchers using grounded theory. We explain how we navigated each stage of the process of conducting a GT study using a collaborative and interdisciplinary approach. The article also presents some key takeaways for researchers to consider when working collaboratively.